(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article analyzes the futurological ideas of Kalygul Bai uulu in the context of the conceptual system of philosophical anthropology. In the history of Kyrgyz philosophical thought, the patriarch of futurologists and sages of Central Asia, Kalygul Bai uulu (1785-1855), stands out in particular, who managed to see behind a single common, behind today’s existence, the face of the future state of society. His anthropo-futurological ideas were ahead of their difficult, contradictory time. He analyzed the attitude of people, tribes, rich and poor, young and old, society and nature, gave advice, expressed his attitude to various processes. Kalygul’s insight was realized through the application of such a cognitive technique as extrapolation of information, knowledge from a single object to its entire classes, from the present stage of the object’s existence to its distant future, from a single, individual object to its groups and classes.